Estimation of Blood Pressure by Image-Free, Wearable Ultrasound - Ana Belen Amado Rey (Artery Research)
Abstract 1.28 billion adults worldwide have high pressure, and only 21% of people have it under control. If high blood pressure (BP) is not diagnosed and treated properly, then there is a high risk for cardiovascular diseases, the main cause of mortality. Ultrasound has emerged as a potential medical imaging system to monitor cardiovascular health. It is comfortable, noninvasive, safe, and a very well-established and well-known technology. However, there are currently no commercial single ultrasound systems to directly quantify vascular parameters, without the need for complex imaging algorithms, additional software-based solutions, and high energy demands that limit portable and prolonged measurements. In this paper, we present the steps to design an image-free novel ultrasound device to continuously extract vital parameters, with a focus on BP. Moreover, as the BP waveforms are amplified toward the periphery (i.e., from the aorta to the radial artery), we applied mathematical models and algorithms, specific to the site of measurement, to accurately extract BP. We validated these algorithms in silico, in vitro, and ex vivo, where tissue and artery phantoms help emulate human physiology. In young subjects, an in silico pulse pressure (PP) correlation of 0.978 and a mean difference of (– 2.85 ± 2.57) mmHg at the radial artery were achieved. The ex vivo PP correlation was 0.986, with a mean difference of (1.72 ± 3.29) mmHg. Soon thereafter, in vivo measurements of BP and stiffness, and their correlation analysis will be performed to corroborate the accuracy of the developed proof-of-concept device.